SGLT-2 Inhibitor: Pilihan Terapi Baru Untuk Penderita DM Tipe 2 - I GUSTI A. A. E. AMANDARI; MADE ARY SARASMITA; NI PUTU U. S. DEWI; MADE WINDA KRISNAYANTI (Universitas Hang Tuah, 2018)
ABSTRACT Type 2 diabetes mellitus (DMT2) is a medical condition characterized by an increase in blood glucose levels exceeding normal limits. World Health Organization (WHO) states that the number of DMT2 patients in Indonesia has increased from 8.4 million patients in 2000 to 21.3 million patients in 2030, which is 90% of them are patients with DMT2. Pathophysiology of DMT2 is a complex process and involves many factors. The ominous octet concept proposed by Ralph DeFronzo plays an important role to explain the pathophysiology of DMT2. The kidneys are organs that have a significant role to control blood glucose to stay within normal limits, thus being considered to be targets of new drug therapies. Sodium glucose co-transporters (SGLTs) such as SGLT-2 facilitate the reabsorption of glucose into plasma. Pharmacokinetics of the SGLT-2 inhibitors generally show good bioavailability when administered orally. DMT2 is a risk factor for chronic kidney disease (CKD) and cardiovascular disease (CVD). The presence of an inhibitory mechanism in SGLT-2 will benefit the reno-cardiovascular system through decrease in blood glucose, weight, and blood pressure. SGLT-2 inhibitors have some favorable adjunctive effects for metabolic syndrome, such as weight loss, decreased blood pressure (especially systolic), as well as decreased serum uric acid